Example Ordinance for Compost Amending Soil in Urban Landscaping - Jovana Radovanovic; James D. McGuire; Jana Caracciolo; Tom Ankersen; Eban Z. Bean (EDIS)
This publication describes an example ordinance that can be used by local governments as a starting point for developing a compost amendment ordinance tailored to their local situation and conditions. Written by Jovana Radovanovic, James D. McGuire, Jana Caracciolo, Tom Ankersen, and Eban Z. Bean, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2021.